Analisis Komprehensif Rasio Profitabilitas dan Rasio Aktivitas dalam Mengukur Kinerja Keuangan PT. Indofood Sukses Makmur TBK Periode 2019-2024 - Ahdzwa Seftia Wibowo; Lisa Solihati; Rudi Sanjaya; Risna Risna; Mirza Linda Aprilyanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study is motivated by the importance of financial performance analysis in the food and beverage industry, which plays a strategic role in the Indonesian economy, particularly amid global economic dynamics during the 2019–2024 period. The objective of this study is to analyze profitability levels, evaluate operational efficiency, and identify financial performance trends of PT Indofood Sukses Makmur Tbk. This research employs a descriptive quantitative approach using secondary data derived from the company’s annual financial statements for the period 2019–2024, obtained from the Indonesia Stock Exchange. The analytical method applied is financial ratio analysis, including profitability ratios (Gross Profit Margin, Net Profit Margin, and Return on Equity) and activity ratios (Total Asset Turnover and Inventory Turnover). The results indicate that the company’s profitability performance is relatively stable, with an average GPM of 32.2%, NPM of 7.1%, and ROE of 12.1%, reflecting its consistent ability to generate profits. From an activity perspective, the average TATO of 0.61 suggests a capital-intensive structure, while an Inventory Turnover of 5.8 times indicates efficient inventory management. Overall, the company demonstrates strong, stable financial performance and adaptability to changing business environments.